A shift away from mutualism under food-deprived conditions in an anemone-dinoflagellate association - Peng, Shao-En; Moret, Alessandro; Chang, Cherilyn; Mayfield, Anderson B.; Ren, Yu-Ting; Chen, Wan-Nan U.; Giordano, Mario; Chen, Chii-Shiarng (PeerJ, 2020)
The mutualistic symbiosis between anthozoans and intra-gastrodermal dinoflagellates of the family Symbiodiniaceae is the functional basis of all coral reef ecosystems, with the latter providing up to 95% of their fixed photosynthate to their hosts in exchange for nutrients. However, recent studies of sponges, jellyfish, and anemones have revealed the potential for this mutualistic relationship to shift to parasitism under stressful conditions. Over a period of eight weeks, we compared the physiological conditions of both inoculated and aposymbiotic anemones (Exaiptasia pallida) that were either fed or starved. By the sixth week, both fed groups of anemones were significantly larger than their starved counterparts. Moreover, inoculated and starved anemones tended to disintegrate into “tissue balls” within eight weeks, and 25% of the samples died; in contrast, starved aposymbiotic anemones required six months to form tissue balls, and no anemones from this group died. Our results show that the dinoflagellates within inoculated anemones may have posed a fatal metabolic burden on their hosts during starvation; this may be because of the need to prioritize their own metabolism and nourishment at the expense of their hosts. Collectively, our study reveals the potential of this dynamic symbiotic association to shift away from mutualism during food-deprived conditions.
Keywords: Anemone; Exaiptasia pallida; Parasitism; Dinoflagellate; Mutualism; Starvation